Irisin Improves High-Fat Diet-Induced Sexual Dysfunction in Obese Male Rats - Yardimci, Ahmet; Ulker, Nazife; Bulmus, Ozgur; Sahin, Elif; Alver, Ahmet; Gungor, Ibrahim Halil; Canpolat, Sinan (Karger, 2022)
Introduction: Obesity is known to cause sexual dysfunction including erectile dysfunction and poor semen quality. Lifestyle modifications such as exercise have increasingly been more recognized to lower the likelihood of having sexual dysfunction or infertility in obese men. In this context, as an exercise-mimetic hormone, irisin has a potential to improve obesity-related reproductive dysfunctions. We aimed to elucidate possible effects of irisin on high-fat diet (HFD)-induced reproductive dysfunction in obese male rats. Methods: Rats were divided into four groups: vehicle, irisin, obese, and obese + irisin. The rats in obese and obese+irisin groups were fed with HFD (60% kcal fat) pellets for 12 weeks to induce obesity, and then obesity-induced sexual dysfunction was confirmed by the sexual behavior test (SBT). Irisin and obese+irisin groups received irisin (100 ng/kg/day) infusion by an s.c. osmotic minipump for 4 weeks after HFD-induced obesity was formed. Results: Irisin did improve a number of measures of copulation, including penile erection, ejaculation, and sexual performance, and also improved sperm morphology and motility and decreased fat-induced testicular damage. It decreased serum leptin levels. On the other hand, irisin did not affect serum luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone. It also increased gene expression of tyrosine hydroxylase (TH) and adrenoceptor alpha 1A (ADRA1A) in the medial preoptic area (mPOA) and nucleus accumbens (NAc). Conclusion: Irisin provided a marked enhancement of HFD-induced decrease in libido, potency, sexual performance, and erection in SBT. Taken together, our results emphasize that irisin has a restorative and improver role in HFD-induced reproductive dysfunctions in obese male rats.
Keywords: Irisin; Exercise; High-fat diet; Obesity; Sexual dysfunction